Організація ризик-аудиту господарської діяльності підприємства - Ларка, Людмила Сергіївна; Шкрьогал, Ольга Володимирівна (НТУ "ХПІ", 2015)
Досліджено етапи організації ризик-аудиту діяльності підприємства. Метою статті є розробка процедур для етапів проведення ризик-аудиту згідно класичному процесу управління. Завданнями статті є систематизація факторів, що впливають на рівень ризику діяльності підприємства, визначення основних процедур проведення ризик-аудиту. Запропоновано заходи для мінімізації рівня ризику. Було застосовано методи аналізу та синтезу. Зроблено висновки про заходи для підвищення ефективності ризик-аудиту на підприємстві.

The phases of company risk audit are investigated. The aim of the article is to develop procedures for the phases of risk-audit according to the classical management process. The objectives of the article are to systematize the factors affecting the level of risk of the enterprise, the definition of the basic procedures of the risk audit. The events to minimize the level of risk are given. The methods of analysis and synthesis are used. Conclusions on activities to improve the effectiveness of risk audit at the enterprise are shown. The conditions to increase the quality of the audit are formulated. Prospects for further research are to develop methodological support procedures for each of the phases of risk-audit of the company.
Organization of risk audit of enterprises economic activity
Keywords: мотивація; контроль; процедури; SWOT-аналіз; motivation; control; procedure